PENGGUNAAN ABU BATU DAN SPLIT DALAM PEMBUATAN PAVING BLOCK - Mulyati, Mulyati (Jurnal Teknologi dan Vokasi, 2023)
This study used stone ash and split as a mixture in the manufacture of paving blocks.  The purpose of this study was to determine the compressive strength and water absorption of paving blocks from the use of stone ash and split.  The mixed ingredients for making paving blocks as a comparison are cement and sand with a composition of 1:8, and the use of cement, stone ash, split with a composition of 1:6:4, 1:8:4, 1:8:8.  Making paving block specimens using a machine with a mold size of 21 cm x 10.5 cm x 6 cm.  Testing of the compressive strength and water absorption of paving blocks was carried out at 28 days of age.  The results of the study used sand and stone ash and split in the manufacture of paving blocks with a ratio of 1:8 and 1:6:4, 1:8:4, 1:8:8, obtained an average compressive strength of 5,.29 and 5.07 MPa, 7.99 MPa, 4.51 MPa respectively, and for water absorption an average of 10,64% and 7.14%, 9.70%, 9.87% respectively.